Pengaruh Ukuran Perusahaan, Leverage dan Kurs terhadap Harga Saham pada Perusahaan Property dan Real Estate yang terdaftar di Bursa Efek Indonesia (BEI) periode 2019-2023 - Andini Taniawaisrin M.A.L; Yamasitha; Nila Pratiwi (GLOBAL SCIENTS PUBLISHER, 2025)
This research aims to determine the influence of company size, leverage and exchange rate on share prices. The object of the research carried out is the Property and Real Estate sector listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The sample collection method used purposive sampling, with a total sample of 16 companies. The analytical method of this research is to use multiple linear regression analysis techniques by testing three hypotheses with the SPSS Version 25 application. The results of this research show that (1) Company size partially affects Stock Prices (2) Leverage partially has an effect on stock prices (3) The exchange rate also has a partial effect on stock prices.